O mercado de tomate em Goiás: estudo sobre o comportamento da cadeia e a evolução da atividade produtiva no setor in natura - Sousa Neto, Renato de (2019)
The tomato tree stands out as one of the most important olive groves for Brazilian agribusiness. The fruit requires costly care for a successful large-scale harvest. In addition to the high cost of cultivation, due to the need for ostensive care with the activity, the tomato has a specificity of loss of biochemical quality that makes it impossible for the fruit to be stored. In the case of tomato, there are two main cultivated plant genres: the table tomato in natura (staked) and the industrial tomato (low). In the midst of this scenario, Goiás stands out as the national leader in tomato production (IBGE, 2014). Given all the importance of the activity in Brazil and its relevance to the state of Goiás, it is generally expected to find an abundance of data and studies that identify the formation of productive and conjuncture links of the chain, since its representativity. This expectation is contradicted when looking for any structural information about the tomato chain in the current literature. The goal of this study is to analyze and analyze the volume and evolution of the production of table tomatoes at the national and regional levels, especially for Goiás, a state currently leader in the cultivation and production of tomato in the country. This objective attends to the need to assist agents participating in the fruit chain in making decisions inherent to the activity.